Implementación de una red inalámbrica de cámaras integrada a un sistema mecatrónico para el monitoreo de entornos residenciales y el manejo remoto de puertas usando MQTT (2022)
In this project, a wireless camera network (RIC) is proposed, composed of cameras as the main sensor, which, connected to a mechatronic system, allows the actuation of DC motors and thus the remote control of doors. The communication between the RIC and the mechatronic system will be managed by an MQTT Broker server. The camera network will be limited to four cameras located within a residence, while the mechatronic system will only have 2 actuation outputs. The process to follow to achieve this purpose consists of five phases: i) The implementation of the RIC for detection by cameras; ii) The construction of the mechatronic system for the actuation of the doors, iii) The integration of both systems through MQTT, iv) Recognize the face of passers-by in order to generate an alarm to support the work of the security guard and v) The evaluation of the proposed solution based on variables such as the door translation speed, motor torque, latency, the number of lost packets, received signal strength (RSSI) and power consumption. Likewise, all this information will be expressed in graphs that will show in detail the behavior of the RIC under different test conditions.